Luke - Kreitzer, Beth; George, Timothy; Manetsch, Scott M. (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2015)
"The Reformation Commentary on Scripture is a twenty-eight-volume biblical commentary bringing the insights of the Reformation to the contemporary church. Incorporating the accurate and readable text of the English standard Version of the Bible (ESV), these volumes assemble exegetical and theological comment on the entire canon of Scripture by a vast array of Reformation-era thinkers and leaders. The series boasts internationally recognized scholars of the history and theology of the Reformation as translators and editors, whose aim is to retrieve the wisdom of the Reformers for the renewal of the church today." -- Back Cover
Abbreviations -- A guide using this commentary -- General introduction -- Introduction to Luke -- Commentary to Luke -- Map of Europe at the time of the reformation -- era figures and works -- Timeline for the Reformation -- Biographical sketches of the Reformation-era figures and works -- Sources for biographical sketches -- Bibliography -- Author and writings index -- Subject index -- Scripture index.
Includes bibliographical references and index.
Print version record.
Keywords: Bible. -- Commentaries; Bible; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Commentaries; Electronic books